AUTOMATED BLOOD BANK SYSTEM USING RASPBERRY PI (International Journal of Food and Nutritional Sciences, 2022)
The "Automated Blood Bank System using Raspberry Pi" is an innovative project aimed at revolutionizing the traditional blood donation and storage process by leveraging IoT (Internet of Things) technology. This system is designed to efficiently manage and automate blood bank operations, ensuring real-time data monitoring, seamless donor registration, and inventory management. The system employs a Raspberry Pi as the central controller, integrating various sensors and modules to monitor critical parameters such as temperature, humidity, and blood levels. The real-time data is displayed on a web interface accessible to both administrators and donors, enhancing transparency and efficiency. The proposed system also features an alert mechanism that notifies administrators of critical conditions, such as low blood levels or temperature deviations, ensuring prompt action. This project aims to reduce human errors, improve resource management, and ultimately save lives by ensuring that blood is available and stored under optimal conditions.